Electrooxidation treatment of simulated wastewater using mixed-metal oxide anodes for bacterial decontamination - Chandra, Poulomi; Choudhury, Diptiman; Verma, Anoop (Comptes Rendus. Chimie)
This study aims to explore the potential use of electro-oxidation (EO) as a decentralized wastewater treatment method. The simulated wastewater comprising bacterial consortium was treated by employing mixed metal oxide (MMO). In particular, a lab-scale batch electrooxidation reactor was used at different operating parameters including NaCl dose ($n$), current density ($j$), and treatment time ($t$) in order to optimize the process using response surface methodology. The efficiency of the treatment process was evaluated in terms of % inactivation and energy consumption which were found to be 99.2% and 0.42 kWh/m$^{3}$, respectively. Under optimal conditions, it was found that the proposed technique’s overall operating cost was 0.189 $/m$^{3}$ taking into consideration the electrical energy consumed and cost of electrodes.